УЎК:631.319.06. Азықлылық цехлары ушын от-шөп майдалағышларды таңлаў - Султанов, Е.К.; Рамазанов, Б.Н.; Жумамуратова, В.Б.; Қарлыбаев, А.М. (FAN va JAMIYAT, 2022)
The article provides recommendations for the ISK-3A reed grinder-mixer in the feed preparation shops of dairy farms in the Republic of Karakalpakstan, as well as provides a technological description of this device.